The relationship between the vegetarian lacto diet and depression in the Sri Sri Jagannath Gaurangga Pasraman Community - Octhovianty Palyngan; I Wayan Westa; Anak Ayu Sri Wahyuni; Ni Ketut Sri Diniari (Indoscholar Publication and the Indonesian Psychiatric Association, 2021)
Background: Depression is one of the most common mental disorders in society. The causes of multifactorial depression are factors: biology, psychology, and socio-culture. Diet is one of the socio-cultural stressors that is thought to cause depression. Vegetarian is one type of diet that reduces animal ingredients and prefers vegetable ingredients. A vegetarian diet is thought to prevent depression. This study aims to determine the relationship of the vegetarian lacto diet with depression in the Sri Sri Jagannath Gaurangga community in Denpasar. Material and Methods: Study participants numbered 59 people in the Sri Sri Jagannath Gaurangga Pasraman community, Denpasar City, aged 18 years or older. Research using cross sectional analytic methods. Measurement of the vegetarian lacto diet using the Indonesian version of the Mediterranean Diet Score (MedDit Score) questionnaire and depression using the Beck Depression Inventory (BDI) questionnaire. Data were analyzed descriptively and using chi square test with significance level of <0.05. Results: The results showed an adequate vegetarian diet that was not depressed by 80% while a good vegetarian lacto diet that was not depressed by 78.8%. There was a negative significant relationship between the vegetarian lacto diet and depression in the Sri Sri Jagannath Gaurangga community of Denpasar (p=0.043). Conclusion: The prevalence of depression in the Sri Sri Jagannath Gaurangga Pasraman community in Denpasar was 20.3%. We found that there was a significant negative relationship between the vegetarian lacto diet with depression.